Effects of Physical Fitness Program on the Quality of Life of the Inmates in Iligan City Amidst COVID-19 Pandemic - Englatiera, Brittany; Colobio, Vanessa Vera R.; Biong, Corazon (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
The purpose of the study was to examine the effects of physical fitness program on the quality of life of the female inmates in Iligan City amidst COVID- 19 pandemic. The study used a quasi-experimental research design. Sixty-eight female inmates were assigned in two groups (controlled and experimental) of 34 participants each group based on non-random criteria. The duration of the physical fitness program for the experimental group was 12 weeks. Control group individuals did not participate in the physical fitness program. A set of questionnaires, which included sections of the respondents’ profile, and a short version of Short Form Health Survey (SF-12), was administered twice to both groups before and after the physical fitness program. The findings of this study revealed that the physical fitness program, regardless of the frequency, intensity, type, and time of participation was significantly associated to the quality of life in terms of general health (P= 0.004), body pain (P= 0.010), vitality (0.023), and emotional state (P= 0.002) of the female inmates (experimental group). Although further study is necessary (e.g., longer fitness program), the present study showed that a 12-week physical fitness program could improve the quality of life of the female inmates. Thus, the researcher recommends that the BJMP continue with the fitness program and further studies be conducted that would assess and validate the effects of fitness program within jail setting.